Optimization of parameters of designed and developed hand-held electrostatic sprayer and its performance evaluation for herbal pesticides. (October 2019) - Patel, M K; Kumar, A; Kumar, P; Jangra, A; kumar, A
Abstract: Electrostatic force field has been exploited in the design and development of a handheld air-assisted electrostatic sprayer for herbal pesticides. Electrostatic spraying is a novel approach for agricultural pesticides applications to increase the mass transfer efficiency, pesticide bio-efficacy, uniform deposition, maximum canopy coverage and liquid pest to reach the hidden areas and underside of the target by reducing the drift of active ingredients of pesticides from the target. A new air-assisted electrostatic sprayer has been designed and developed for small scale farms with a specific focus on rural developing economies. In this work, experiments were carried out with four types of herbal pesticides and one chemical pesticide to evaluate and compare the performance of developed electrostatic sprayer. The results are characterized in terms of depended variable i.e. charge-to-mass ratio by varying independent variables such as applied voltage, air pressure, conductivity and density of liquid. The droplets are charged more than 8 mC/kg with an applied voltage of 1.5 kV at a flow rate of 110 ml/min and air pressure of 40 psi which is more than desirable to achieve the wraparound effect. This nozzle is light weight, highly efficient, reduces pesticide use and human health risks, and eco-friendly.